Potret Perilaku Koruptif di Kalangan Mahasiswa Akuntansi - Mutiya Nur Assyifa; Yeni Agustina; Susi Susi (Jurnal Akuntansi Publik Nusantara, 2024)
This study aims to identify the corruptive behavior among accounting students and analyze the factors influencing such behavior. The investigated actions include cheating, document manipulation, absenteeism through proxies, offering gratuities to lecturers, and misuse of scholarship funds. The research adopts a quantitative approach, collecting data through questionnaires distributed to accounting students at various educational levels. The data analysis reveals that corruptive behaviors are relatively common. Most respondents admitted to engaging in actions like cheating and absenteeism through proxies, while a smaller proportion participated in document manipulation or offering gratuities.The findings suggest that academic experiences, such as having attended professional ethics or audit courses, contribute to shaping students’ awareness of integrity. However, academic pressure and a permissive campus culture often act as driving forces behind corruptive behavior. This study highlights the necessity of strengthening ethics education within accounting curricula to instill the value of integrity. Additionally, institutional measures such as enhanced supervision, technology-based attendance systems, and awareness campaigns are essential to fostering a more transparent and accountable academic culture.